Ohne Worte: Vocality and Instrumentality in 19th-Century Music - Brooks, William; Torbianelli, Edoardo; Roudet, Jeanne; Bartoli, Jean-Pierre; Seaton, Douglass; Mossburger, Hubert (Leuven Leuven University Press, 2014)
Vocality and Instrumentality in 19th-Century MusicThe musical thought and practice of canonical composersWhat can music tell us without words? Can it depict scenes, narrate stories, elucidate beliefs? And can it be an instrument through which we access the inner lives not only of musicians from the past but of ourselves, today?In Ohne Worte five scholars and performers probe these and related questions to illuminate both the experience and performance of nineteenth-century music. Drawing on a rich range of sources, they reveal the musical thought and practice of canonical composers like Berlioz, Mendelssohn, and Schumann. Their work challenges us to reconsider our musical practices and the voices manifested in them, and it encourages the creation of an art that is both historical and transcendental.ContributorsJean-Pierre Bartoli (Université ParisSorbonne), Hubert Moßburger (Staatlichen Hochschule für Musik und Darstellende Kunst Stuttgart), Jeanne Roudet (Université ParisSorbonne), Douglass Seaton (Florida State University School of Music), Edoardo Torbianelli (Hochschule der Künste Bern)
Keywords: Berlioz, Hector -- 1803-1869; Mendelssohn-Bartholdy, Felix -- 1809-1847; Schumann, Robert -- 1810-1856; 19th Century (1801-1900); Instrumental music; Music philosophy and esthetics; Artistic research